Penguatan Soft Skills Pelajar melalui Sosialisasi Partisipatif di SMP Swasta Masyarakat Damai - Eliagus Telaumbanua; Asmaweti Zai; Kristina Natalia Zendrato; Arini Rahmi Mendrofa; Misdar Ningsih Kurinci; Taufiq Ihsan; Jelita Telaumbanua (Lembaga Dongan Dosen, 2026)
Soft skills are non-academic competencies that help students communicate, collaborate, manage time, solve problems, and adapt to change. This Community Service Program aimed to strengthen students' understanding of the meaning and application of soft skills as a foundation for learning success, social interaction, and future readiness. The activity was conducted on 15 June 2026 at SMP Swasta Masyarakat Damai, Gunungsitoli City, through participatory socialization combining a presentation, discussion, question-and-answer session, quiz, group work, and simple reflection. The materials covered communication, teamwork, self-confidence, leadership, responsibility, time management, problem solving, and adaptability. The activity showed that all planned stages were completed and that students were provided with a participatory space to connect the materials with their daily learning experiences. Since no pre-test and post-test instruments were used, the reported results are limited to process achievements and cannot be interpreted as quantitative evidence of improved competence. The activity underlines the importance of sustained soft-skills strengthening through classroom learning, group work, student organizations, and simple measurable evaluation.